Socially sustainable neighborhoods: Special reference to the Egyptian context - Azzam, Alia Omar (AUC Knowledge Fountain, 2017)
Urban social sustainability has become one of the rising topics drawing the attention of urbanists and policymakers all over the world. Yet, in Egypt, the concept is not given enough consideration in the current urban development context. It is still quite immature in both theory and practice, especially in new cities where social problems can be challenges to the sustainability of communities. In addition, a neighborhood is found to be a critical urban scale that affects both individuals and the society as a whole. Therefore, this research sheds light on the importance of embracing the concept of urban social sustainability within the neighborhood scale as a way of achieving a better overall urban sustainability in Egypt. The research questions the factors that build a socially sustainable neighborhood and their relevance in the context of Egyptian new cities. To answer this, a comprehensive literature review was conducted and a qualitative methodology was adopted. Research tools such as face-to-face interviews and direct observations were used in a case study analysis to achieve a clearer understanding of the concept within the Egyptian context. The findings revealed that the selected case study - South Academy A in New Cairo City - has poor social sustainability mainly because of factors embedded in its urban form and planning, in addition to the centralized urban governance system; both have resulted in limited accessibility and low community wellbeing. The findings also highlight the importance of the urban form dimension as a basic principle in achieving a socially sustainable neighborhood, and it calls for a paradigm shift in the current Egyptian urban planning and policymaking. Conclusively, the research proposes a guiding framework and a set of recommendations that could be utilized in an attempt towards a more socially sustainable urban situation in Egypt.